2009
DOI: 10.1111/j.1600-6143.2009.02652.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin Improves Early Outcomes After Intraportal Islet Transplantation

Abstract: Primary islet nonfunction due to an instant blood mediated inflammatory reaction (IBMIR) leads to an increase in donor islet mass required to achieve euglycemia. In the presence of thrombin, thrombomodulin generates activated protein C (APC), which limits procoagulant and proinflammatory responses. In this study, we postulated that liposomal formulations of thrombomodulin (lipo-TM), due to its propensity for preferential uptake in the liver, would enhance intraportal engraftment of allogeneic islets by inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 54 publications
(58 reference statements)
0
30
2
Order By: Relevance
“…Human islets are subjected to both immunological and nonimmunological insults in the immediate posttransplantation period leading to islet cell death and graft failure (30)(31)(32)(33). VEGF is an angiogenic factor that is known to enhance survival of both endothelial and other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Human islets are subjected to both immunological and nonimmunological insults in the immediate posttransplantation period leading to islet cell death and graft failure (30)(31)(32)(33). VEGF is an angiogenic factor that is known to enhance survival of both endothelial and other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this approach, a monoclonal anti-TF antibody (CNTO859) has been shown to enhance engraftment in a non-human primate marginal mass model (Berman et al, 2007). In addition to direct inhibition of TF, inhibition of the coagulation system at various stages of activation, for example by using the thrombin inhibitor Melagatran (Ozmen et al, 2002), active siteinactivated FVII (iFVIIa) (Moberg et al, 2002a), N-acetylcysteine (Beuneu et al, 2007), activated protein C (APC) (Contreras et al, 2004), anti-GP IIb/IIIa in combination with APC (Akima et al, 2009) or thrombomodulin (Cui et al, 2009), is able inhibit thromboinflammation in vitro or in vivo. As already mentioned, the complement inhibitor compstatin inhibits the release of C-peptide from pancreatic cells exposed to human plasma .…”
Section: Systemic Administrationmentioning
confidence: 99%
“…High doses of heparin and complement inhibitors such as low molecular weight dextran sulfate and melagatran were able to overcome the islet destruction by inhibiting the IBMIR. [6][7][8][9][10] However, these drugs are limited in terms of their efficacy and safety because of a narrow therapeutic window and poor penetration into the thrombus. Furthermore, several literatures have demonstrated that isolated islets express at least 50 inflammation-associated genes, including those for monocyte chemotactic protein-1, interleukin-8, vascular DOI 10.1007/s13233-011-0904-y *Corresponding Author.…”
Section: Introductionmentioning
confidence: 99%